Vericiguat reduces atrial fibrillation recurrence by alleviating myocardial fibrosis via the TGF-β1/Smad2/3 pathway - Xiaolin Sun; Yawen Sheng; Pei Xu; Qian Peng; Zhongbao Ruan (PLoS ONE, 2025)
Atrial fibrillation (AF) and heart failure (HF) are mutually reinforcing, and the prognosis for both diseases is poor. Vericiguat is the first oral soluble guanylate cyclase (sGC) stimulator to be approved for the treatment of symptomatic, ejection fraction-reduced chronic heart failure (HFrEF) in adults. It exerts a general therapeutic effect on cardiovascular diseases, with a particular efficacy in the treatment of HF. However, it remains uncertain whether vericiguat exerts a therapeutic effect on atrial fibrillation. The objective of this study was to investigate the potential mechanism of vericiguat in the treatment of atrial fibrillation. A retrospective analysis was conducted to investigate the effects of vericiguat on patients with heart failure and paroxysmal AF. Furthermore, the effects of vericiguat on AF and the degree of myocardial fibrosis in rat AF models and cells were observed. It was found that vericiguat may control the recurrenceof AF in clinical studies and can control the fibrosis of AF rats in vivo and in vitro experiments. RNA-Seq sequencing revealed that the TGF-β1/Smad pathway in cells treated with vericiguat was significantly enriched. In vitro validation demonstrated that the anti-fibrotic effect of Vericiguat was weakened by the TGF-β1/Smad pathway when Protein Kinase G (PKG) was knocked down. The findings indicate that vericiguat may inhibit myocardial fibroblast activation and collagen synthesis via the TGF-β1/Smad pathway, thereby exerting a controlling effect on the recurrence of atrial fibrillation.